The value of reflective journaling with advanced piano students. Issue 6 (1st November 2016) - Woronchak, Meganne; Comeau, Gilles
Abstract: Benefits to using a reflective journal include developing critical awareness and new perspective, problem-solving skills, and independent learning skills. The training of advanced piano students could be enhanced by the addition of journals to assist with their piano practice, specifically when learning new repertoire. Using the model by Plack and colleagues for developing and assessing reflection in reflective journal entries, we examined the journal entries of 18 advanced piano students to explore the development of reflection over a period of four weeks. Results suggest that reflectively trained piano students develop more critical reflection compared to a control group. Reflectively trained students perceive the same benefits to journaling as their counterparts in other disciplines. The most frequently referenced reflective elements include listing practice strategies and expressing feelings about the learning process. The reflective training model used in this study can be implemented by piano teachers and piano students.